Effect analysis of small‐problem‐based teaching method for improving students’ problem‐solving ability in the experiment of power electronics course - Guopeng Zhao (IET Circuits, Devices and Systems, 2021)
Abstract To make students understand the working principle of circuits in the course of Experiment of Power Electronics more deeply, the author introduces a small‐problem‐based teaching method to help students master the relevant curriculum content and enhance their ability of independent problem‐solving within 1 or 2 days for balancing the contradiction between course time and burden. Teachers present some small questions according to the basic principles of circuits, and students analyse the problems theoretically. Then students get the answers and verify the conclusions through simulations and laboratory experiments. Furthermore, for comparison of the source harmonic current and the maximum line current for three types of three‐phase ac voltage‐regulating circuits with different connection modes―the three‐phase four‐wire star connection mode, the three‐phase three‐wire star connection mode and the branch‐controlled triangle connection mode―are used as an example to explain the proposed teaching method. Through theoretical analysis, simulation and experimental verification of students, three kinds of circuits are compared, and the conclusions are drawn. Based on the analysis of students’ problem‐solving process and results, it can be seen that most students can complete and get correct conclusions independently. The proposed method can improve the students’ problem‐solving ability.